Reconstruction of Consumer Protection Law in the Settlement of Islamic Banking Disputes - Gema Rahmadani; Zulkarnain Nasution; Pagar Pagar; Ong Argo Victoria (Universitas Lampung, 2025)
The rapid growth of Islamic banking in Indonesia has not been matched by an adequate consumer protection framework, particularly in resolving disputes between customers and Islamic banking institutions. Law No. 8 of 1999 on Consumer Protection remains general and does not accommodate the specific characteristics of Islamic economic law, creating normative inconsistencies and ambiguity in dispute resolution. This study uses a normative legal approach to analyze legislation, DSN-MUI fatwas, and court decisions, and finds a regulatory gap rooted in contractual justice and maqashid syariah principles. This gap risks disadvantaging consumers, especially regarding transparency, the prohibition of usury, and protection from harmful practices such as gharar and maysir. The study concludes that reconstructing consumer protection law to incorporate Sharia-based norms and clearer dispute resolution mechanisms is essential for realizing a fair and sustainable Islamic banking system in Indonesia.